Imagining the Unimaginable: Narratives of the Big Bang: Time, Space, Matter, Energy - Barry Wood (Journal of Big History, 2018)
The term big bang has an uneasy history of problematic and misleading implications. As a derogatory and simplistic metaphor it is incompatible with current understandings of Planck time, inflationary theory, self-organizing dynamics, and emergent complexity. Scientific theory is judged and accepted as much by vocabulary as by content; content-specific nomenclature is a crucial key to understanding. Additionally, imaginative nomenclature that triggers a narrative meets the human need for a relevant story. Creative descriptions for the big bang that reformat it as a complementary cluster of stories are herein proposed with acronyms appropriate to the action of the big bang and meanings consistent with current science; approaches through analytical physics and complex mathematics are here replaced with series of suggestive narratives. Together, they combine to create a multi-strand narrative compatible with our present understanding of cosmic history understood as the Grand Sequence or the Big Story. Additionally the acronyms central to this presentation emphasize that the foundations of reality as we know it—Time, Space, Matter, and Energy—did not exist before the big bang but were in fact created in that event. Anyone venturing into astronomy or cosmology inevitably has to grapple with the big bang. While there are more complex topics in science—quantum physics, for instance, or cell signaling—big bang cosmology challenges our customary experience and understanding of the world. It is simply impossible to imagine how an entire universe could unfold from next to nothing or how time and space—the apparent containers of everything we know—could have come into existence rather than always existing. Lawrence Krauss (2012) makes “a universe from nothing” seem simple, logical, and inevitable; most of us find it otherwise. The following notes provide a brief history of the big bang idea, its eventual acceptance, and current understandings organized into some unique ways to historicize or narrativize what we might more congenially call the big beginning or the first event.